ADALINE Robust Multistep Training Algorithm - Rudenko, O.G.; Bezsonov, O.O. (Control systems & computers, 2020)
The article considers the multi-step ADALINE training algorithm when using the correntropy information criterion as a learning criterion, determines the conditions for the convergence of the algorithm, and shows that in the steady state the resulting estimate is unbiased. The importance of choosing the width of the Gaussian core, which affects the convergence rate of the estimation algorithms and the error in the steady state, is noted, and the feasibility of developing procedures for adaptive correction of the core width is indicated. У статті розглянуто багатокроковий алгоритм навчання АДАЛІНИ за використання в якості критерію навчання інформаційного критерію коррентропіі, визначені умови збіжності цього алгоритму і показано, що в сталому режимі одержана оцінка є незміщеною. Відзначено важливість вибору ширини Гауссова ядра, що впливає на швидкість збіжності алгоритмів оцінювання та помилку в сталому режимі, і вказано на доцільність розробки процедур адаптивної корекції ширини ядра. В статье рассмотрен многошаговый алгоритм обучения АДАЛИНЫ при использовании в качестве критерия обучения информационного критерия коррэнтропии, определены условия сходимости алгоритма и показано, что в установившемся режиме получаемая оценка является несмещенной. Отмечена важность выбора ширины Гауссова ядра, влияющей на скорость сходимости алгоритмов оценивания и ошибку в установившемся режиме, и указано на целесообразность разработки процедур адаптивной коррекции ширины ядра.